music workshop for children and adolescents, ethical-political clinic and training: reports of student experiences - malta oliveira, stephan; leonor chaves carvalho, lissa; da silva, danielle fernanda; de freitas melo, ana carolina; pereira jacques, lucas; justen dos santos, anna beatriz (childhood & philosophy, 2024)
With this article, we seek to investigate the impact of the praxis of a University Extension Project, which consists of a series of music workshops for children and adolescents with what we call autism or other neurodivergences. Within the student training, we took into account the clinical and ethical dimensions of the extension action. We divided the methodology into two parts: the first corresponds to the narrative-type bibliographic review, through which we approach texts on the phenomenology of life and the ethics of alterity, community and liberation; the second part concerns the experiential reports made by the students participating in the Project and co-authors of this article. The students answered questions related to the two thematic axes constructed a priori: the impact of the Music Workshop on their training and their perception of the clinical and ethical dimensions of the Project. We evaluated the narratives through content analysis, from which we constructed the following categories of analysis: transformative impact of the Workshop’s praxis; and biomedical model and critical thinking. Referring to axis 1:art, embracement and therapeutic potential; people who do not fit a diagnosis; and an ethical-political clinic, referring to axis 2. We conclude that extension action has had a positive impact on student training, contributing to a non-normalizing aesthetic, ethical and political clinic, which enables the release of life forces, affirmation of life in its multiplicity, and above all, of those people who have had and continue to have their lives denied and invisibilized by the dominant production system (economic and discursive)